Enhanced hydrogen production with photo-induced phase transformation and cocatalyst loading - ÖZKAYA, ALİ RIZA; KOCA, ATIF (WILEY, 2019)
In this study, reduced graphene oxide (RGO)-Cd(1 - x)ZnxS nanocomposites have been synthesized with the solvothermal method in one pot. Moreover Pt, Ru, and Rh nanoparticles have been loaded on the RGO-Cd(1 - x)ZnxS nanocomposites as cocatalysts with the aim of increasing the photocatalytic (PC) performance for hydrogen evolution reaction. The structure of Cd(1 - x)ZnxS blend transforms from cubic to hexagonal structure during the PC hydrogen evolution reaction (PCHER) at the room temperature. This photo-induced phase transformation (PIPT) enhances not only the hydrogen evolution rate, but also the stability of the photocatalysts. Interestingly, RGO triggers the PIPT process only during the PCHER under solar light illumination. On the other hand, the loading of Pt, Ru, and Rh cocatalysts do not affect the PIPT process. However, they enhance the PC and photoelectrochemical (PEC) hydrogen production activity of RGO-Cd(1 - x)ZnxS photocatalyst. PEC performance increases about 5.5 times when Pt (5%) and RGO are added to the Cd0.60Zn0.40S catalyst. RGO-Cd0.60Zn0.40S including 1.5% Rh photocatalyst reaches a remarkable PC hydrogen production rate of 135 mu molh(-1) with QE of 23.3% at 460 nm. Therefore, Rh cocatalyst appears as a good alternative to Pt.
Keywords: cocatalyst effect photocatalyst; hydrogen production; photo-induced phase transformation; reduced graphene oxide; solar light irradiation; REDUCED GRAPHENE OXIDE; NANOCOMPOSITE; TRANSITION; EVOLUTION; WATER; SIZE; PHOTOCATALYSTS; NANOPARTICLES; COMPOSITES